Twisted twenty-six [large type] - Evanovich, Janet (Evanovich, Janet. Stephanie Plum novel, 2019)
Grandma Mazur is a widow...again. This time her marriage lasted a whole 45 minutes. The unlucky groom was one Jimmy Rosolli, local gangster, lothario (senior division) and heart attack waiting to happen...well, the waiting's over. It's a sad day, but if she can't have Jimmy at least Grandma can have all the attention she wants as the dutiful widow. But some kinds of attention are not welcomed, particularly when Jimmy's former "business partners" are convinced that his widow is keeping the keys to their financial success for herself. As someone who has spent an entire career finding bad guys, a set of missing keys should be no challenge for Stephanie Plum. Problem is, the facts are as twisted as a boardwalk pretzel with mustard.